2012
DOI: 10.5539/jas.v4n2p21
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Root Growth and Distribution in Maize from the Black Soil Region of NE China

Abstract: Root growth is related to its water and mineral uptake. The structure and architecture of the root system is influenced by soil properties. Better understanding of root architecture and growth dynamics of maize grown on black soil may lead to more efficient use of applied nutrients and water by maize. Maize (Zea mays L.), cultivar Yedan 13, was grown in a black soil field in large root boxes in 2007. Plants were regularly sampled and the following data were recorded: number of emerged roots per phytomer, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The slower development of large diameter roots could also reduce inter-plant competition in monoculture. Roots in the third and younger nodes have steeper angles and greater rooting depth, depending on genotype and soil conditions (Yamazaki and Kaeriyama, 1982; Hoppe et al , 1986; Araki et al , 2000; Liu et al , 2012b; York and Lynch, 2015), supporting the potential importance of larger diameter roots in penetrating deep soil for mobile resources. The functional utility and trade-offs of these root anatomical phenes under different environmental conditions require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower development of large diameter roots could also reduce inter-plant competition in monoculture. Roots in the third and younger nodes have steeper angles and greater rooting depth, depending on genotype and soil conditions (Yamazaki and Kaeriyama, 1982; Hoppe et al , 1986; Araki et al , 2000; Liu et al , 2012b; York and Lynch, 2015), supporting the potential importance of larger diameter roots in penetrating deep soil for mobile resources. The functional utility and trade-offs of these root anatomical phenes under different environmental conditions require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Gaudin et al , 2011; Gao et al , 2015). A few root anatomical and architectural phenotypes in maize have been evaluated in multiple nodes in the field, typically in one or two genotypes (Yamazaki and Kaeriyama, 1982; Hoppe et al , 1986; Girardin et al , 1987; Demotes-Mainard and Pellerin, 1992; Jordan et al , 1993; Aguirrezabal et al , 1994; Pellerin, 1994; Liu et al , 2012b). Stamp and Kiel (1992) characterized 28 hybrid genotypes and evaluated six nodes with a focus on metaxylem vessel phenes, and Mano et al (2006) evaluated aerenchyma formation across root nodes and positions in multiple Zea species.…”
Section: Discussionmentioning
confidence: 99%
“…Root diameter has been shown to have a significant influence on the ability of roots to penetrate into the soil 11 , extract water and nutrient in deep soil layers and translocate to aerial parts of the plant. A research study demonstrated that root length density, root weight density, root volume density, and the root diameter of crops are positively related to soil water availability 46 . In the present study, the root diameter of maize crop increased gradually from V7 to V9 stage, rapidly from V12 to R1 and decreased after that to the R6 stage, and was significantly higher in paclobutrazol treatments than untreated control, at all growth stages in 2015 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Because many previous studies have shown that ∼80% of maize roots are concentrated in soil layers between 0 and 40 cm (Liu et al, 2012; Bu et al, 2013; Gao et al, 2014; Zhou et al, 2015), only root samples from the 0‐ to 40‐cm soil layer were taken in this study. At the heading–filling and maturing growth stages, three maize plants with uniform growth were selected as the samples for measuring maize roots.…”
Section: Methodsmentioning
confidence: 99%